Inhibitions of monoamine oxidases and acetylcholinesterase by 1-methyl, 5-phenyl substituted thiosemicarbazones: Synthesis, biochemical, and computational investigations. (December 2020) - Mathew, Githa Elizabeth; Oh, Jong Min; Mohan, Kumar; Kumudhavalli, M.V.; Jayanthi, Sivaraman; Kim, Hoon; Mathew, Bijo
Graphical abstract: Highlights: Eleven methylthiosemicarbazones were prepared and characterised. Inhibitory activities against monoamine oxidase (MAO) and acetylcholinesterase were evaluated. Compound MT5 was non-toxic, and reversible competitive inhibitor for MAO-B (IC50 = 8.77 μM). MT5 binding was stabilized by hydrogen bonding to Cys172 and π–π hydrophobic interaction with Tyr326 of MAO-B. MT5 may be considered a potential compound for the treatment of neurodegenerative disorders. Abstract: A series of eleven 1-methyl, 5-phenyl substituted thiosemicarbazones (MT1–MT11 ) with the phenyl ring substitutions were prepared and investigated for their inhibitory activities against monoamine oxidases (MAOs) and acetylcholinesterase (AChE). [4-(dimethylamino) phenyl]methylidene